A Phenome-Wide Mendelian Randomization and Colocalization Study Reveals Genetic Association Between PBC and Other Autoimmune Disorders - Shuyi Shi; Minghui Liu; Haonan Gao; Fang Liu; Yuhu Song (Canadian Journal of Gastroenterology and Hepatology)
Conclusions: Our study revealed genetic association between PBC and hypothyroidism through a phenome-wide Mendelian randomization, and then, colocalization identified two potential drug targets for hypothyroidism.